2021
DOI: 10.1177/21514593211046407
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life, Patient Satisfaction and Rehabilitation in Patients With a Low Energy Fracture—Part III of an Observational Study

Abstract: Introduction Due to the aging population the incidence of Low Energy Fractures (LEF) increases. LEF have high mortality and morbidity rates and often cause elderly to lose independence. Patient-reported outcomes, such as Quality of Life (QoL) and patient satisfaction (PS) are needed to evaluate treatment, estimate cost-benefit analyses, and to improve clinical decision-making and patient-centered care. Objective The primary goal was to evaluate QoL and PS in patients with LEF, and to compare QoL scores to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…For instance, Chiang et al [ 22 ] and Imai et al [ 23 ] reported mean BI scores of 71.1 and 71.9 points at 1- and 2-year post-hip fracture treatment, respectively. Similarly, our mean 1-year EQ-VAS score (77.0 ± 17.5) is comparable to the mean of 67 ± 2 reported by Svedbom et al [ 24 ] and the mean of 80 ± 10 found by van der Vet et al [ 25 ]…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For instance, Chiang et al [ 22 ] and Imai et al [ 23 ] reported mean BI scores of 71.1 and 71.9 points at 1- and 2-year post-hip fracture treatment, respectively. Similarly, our mean 1-year EQ-VAS score (77.0 ± 17.5) is comparable to the mean of 67 ± 2 reported by Svedbom et al [ 24 ] and the mean of 80 ± 10 found by van der Vet et al [ 25 ]…”
Section: Discussionsupporting
confidence: 91%
“…For instance, Chiang et al [22] and Imai et al [23] reported mean BI scores of 71.1 and 71.9 points at 1-and 2-year post-hip fracture treatment, respectively. Similarly, our mean 1-year EQ-VAS score (77.0 ± 17.5) is comparable to the mean of 67 ± 2 reported by Svedbom et al [24] and the mean of 80 ± 10 found by van der Vet et al [25] Our 1-and 3-year mortality rates were 13.9% and 20.4%, respectively. These numbers were compatible with those reported in a previous systematic review and meta-analysis of various centers with an FLS care model [8,19].…”
Section: Discussionsupporting
confidence: 89%
“…Earlier literature on PROs in elderly patients with a hip fracture shows that a hip fracture negatively affects PROs such as Quality of Life (QoL), and that Fear of Falling is increased after a hip fracture, thereby increasing the risk of a secondary fracture 7. PROs are frequently used in recent hip fracture studies researching different types of treatment, or studies investigating the potential benefit of comanaged care pathways (ie, orthogeriatric care pathways) 8 9…”
Section: Introductionmentioning
confidence: 99%